Control of Automatic Food Drive-Through System using Programmable Logic Controller (PLC) - Ab Rashid, Mohd Zamzuri; Ahmad Izzuddin, Tarmizi; Abas, Norafizah; Hasim, Norhaslinda; Abd Azis, Fadilah; Mohd Aras, Mohd Shahrieel (2013)
This project is about automatic control for food drive through system controlled via Programmable Logic Controller (PLC) and this system consists of food drive through with two lanes and no human operator is required to operate this food drive through. The difference of this automatic control drive through system compared with the current drive through system is the current system required a few operators to operate the system. This automatic control drive through system is fully operated by machine, like order and payment machine and conveyor which deliver the food while human only needed and involved only to prepare the food. Since there are two lanes involved in this system, the machine installed has two order and payment machines, two ticket verification machines, two conveyors which connect to the kitchen and four sensors to detect the vehicles.